Assessment of Brazilian children’s anxiety during the second year of the COVID-19 pandemic through cross-sectional interviews at schools - Crepalde, Patrícia Aparecida Francelino; Garcia de Avila, Marla Andréia; Minharro, Michelle Cristine de Oliveira; Castro, Meire Cristina Novelli; Teixeira, Tatiane Roberta Fernandes; Hamamoto Filho, Pedro Tadao; Nilsson, Stefan (Frontiers in Public Health, 2025)
IntroductionThis cross-sectional study aimed to assess anxiety prevalence among schoolchildren and associated factors following their return to in-person classes during the COVID-19 pandemic.MethodsThis study was conducted in June 2022 and involved children aged 6–12 years and their parents at four public schools in Brazil. Anxiety levels were assessed using the Children’s Anxiety Questionnaire (CAQ; scores of 4–12) and visual analog scale (VAS; scores of 0–10). Of 733 children, 54% were girls (average age, 8.7 ± 1.87 years), and most of the included parents were mothers (84%).ResultsBased on Brazilian CAQ scores of ≥9 and VAS scores of >7, anxiety prevalence was 13.5 and 6.7%, respectively. Using logistic regression, CAQ scores of ≥9 and VAS scores of >7 were associated with the children’s ages. Each additional year of children’s age raised the odds of anxiety (CAQ ≥ 9) by 10%. For the VAS scores, each additional year of children’s age increased the odds of anxiety (VAS > 7) by 30%.DiscussionThese findings showed a lower prevalence than those reported at the beginning and one year after the start of the COVID-19 pandemic, further emphasizing the need for public health interventions targeting different age groups.